Book and Journal Reviews. Issue 1 (1st March 2003) - Hartley, Peter; Pelik, Rowena; Woodfield, Richard
Learning in Groups, a handbook for improving group work, Jaques, D. (2000), 3rd edn., London: Kogan Page, 310 pp, ISBN 0-7494-3091-5 (paperback).The Module and Programme Development Handbook, Moon, J. (2002), London: Kogan Page, ISBN 0-7494-3745-6. Also available in a A4 photocopiable loose-leaf ring-bound format for use by staff developers (ISBN 0-7494-3746-4).Journal of Visual Arts Practice, Biggs, I. (ed.) (2000), 1: 1-3, Bristol: Intellect, ISSN 1470-2029